A Cyber Crime Analysis of Two Call Dimensional Effects in Internet Traffic - Virendra Kumar Tiwari; D. Shukla (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
The stuff of internet users increasing with the every moment of time, due to this huge lead of traffic grows on the wide area networks. Some users have crime category behavior and have attitudes of criminals like hacking the site, blocking the mail, chatting unauthorized users etc. Every service provider wants to increase his traffic share and way, which creates the competition among the providers. When users get the connectivity he initiates the crime activity. In this paper invested the effect of different categories crime users on the internet traffic sharing under the Markov Chain model. There are two groups of users (i) Crime users (ii) Noncrime users. Further crime users divided into two group Fully-crime users and Partially Crime users. Simulation study is performing to analysis the better proportion of traffic by the users.